Pengaruh Strategi Pemasaran dan Inovasi Produk Terhadap Keputusan Pembelian pada Furniture Hj Vera di Kota Karawang - Regita Kusuma Dewi; Puji Isyanto; Neni Sumarni (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This is a The research aims to determine marketing strategies and product innovation on purchasing decisions for Hj Vera Furniture in Karawang City. The method used in this research is a quantitative method, this research was conducted on Hj Vera Furniture in Karawang City with a total research sample of 96 people with the criteria of consumers who had previously purchased Hj Vera Furniture in Karawang City, using a purpisive sampling method. The multiple linear regression analysis model used in this research uses the f test and t test with a significance threshold of 5%. The findings show that there is a partial contribution between marketing strategies and purchasing decisions at Hj Vera Furniture in Karawang City. The research results obtained are the influence of marketing strategy and product innovation on purchasing decisions at HJ Vera Furniture in Karawang City, there is an influence from all variables.